Anticorpos Monoclonais contra Listeria spp.: Produção, Caracterização e Aplicação em Métodos Diagnósticos - Mendonça, Marcelo (2011)
The conventional methods used to detect the Listeria monocytogenes in foods are laborious and expensive, requiring several days for final identification. Monoclonal antibody (MAb) based immunoassays are highly specific and rapid to perform, especially when MAbs are raised to conserved virulence factors in the pathogen. Among diverse virulence factors of L. monocytogenes, the surface protein internalin A (InlA) is one of the most well-known and characterized protein, being an excellent target as it is highly exposed on the surface and exclusive of pathogenic species. In this work we report the production, characterization and use of a panel of MAbs against InlA (2D12, 3B7, 4E4), and a MAb (3F8) which specifically recognizes all bacteria belonging the genus Listeria. MAbs were produced by the immunization of BALB/c mice with a recombinant InlA together with heat killed L. monocytogenes. The MAbs produced showed excellent reativities by indirect ELISA, Western blot and immunofluorescence. A Cy5 conjugated anti-InlA MAb-2D12 was used as detection antibody for L. monocytogenes in a sandwich-like fiber optic immunoassay. Using MAb-2D12 as capture antibody on the waveguides, the limit of detection was ~3 x 102 CFU.mL-1, and when MAb-3F8 was used for capture the limit of detection was ~1 x 105 CFU.mL-1. Furthermore, MAbs 2D12 and 3F8 were used to coat paramagnetic beads and tested in the immunomagnetic separation (IMS) of L. monocytogenes from pure cultures, and artificially contaminated cheeses and hotdogs. After IMS capture, bacteria were released from the beads, used in the fiber optic assay or plated on agar for counting. In parallel, the capture of L. monocytogenes was confirmed by real-time qPCR and light-scattering technology (BARDOT). Using IMS to concentrate and separate L. monocytogenes, followed by a fiber optic platform, it was possible to detect in less than 22 h, approximately 40 CFU/g of L. monocytogenesi, even in the presence of L. innocua in cheese and hot dogs artificially contaminated. In addition, using mass spectrometry (MALDI-TOF-MS) the protein to which MAb-3F8 binds, was identified as fructose 1,6-bisphosphate aldolase (FBA). The results presented in this work indicate that using both systems together, the IMS and fiber optic immunosensor, were more reliable and faster, and could be applied in the routinely for detection of L. monocytogenes in food. Moreover, both MAbs have the potential to useful in others biosensor platforms, as well as in other detection and functionality immunoassays for InlA and FBA in Listeria.